2010
DOI: 10.1080/01634372.2010.489936
|View full text |Cite
|
Sign up to set email alerts
|

Sharing Meals With Institutionalized People With Dementia: A Natural Experiment

Abstract: Nutritional deficiency can have dramatic effects on the physical and psychological status of older adults. Although food supplements can enhance nutritional status, several authors suggest that more ecological means could also have beneficial impacts. Therefore, a natural experiment was conducted to study the impact of changed mealtime experiences for people with Alzheimer-type dementia. Two special care units (in separate facilities) in France were included in this study: one implemented shared meal times bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
86
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(88 citation statements)
references
References 24 publications
1
86
0
1
Order By: Relevance
“…However, a limited number of studies have quantified the impact of contextual improvement on food intake and/or on the nutritional status of institutionalized people (Abbott et al, 2013). Some of them focused on the effectiveness of a single change such as providing smaller portions (Cluskey & Dunton, 1999), switching from a prepared tray to a bulk service (Shatenstein & Ferland, 2000), having the staff share the meals with the residents (Charras & Frémontier, 2010), enhancing the colour contrast of the crockery that food was served on (Dunne, Neargarder, Cipolloni, & Cronin-Golomb, 2004), improving lighting (Brush, 2002) or diffusing music in the dining room (Ragneskog, Brane, Karlsson, & Kihlgren, 1996;Thomas & Smith, 2009). Six studies assessed large-scale changes which mainly aimed at shifting the dining room from an institutional appearance to more home-like setting ( Table 1).…”
Section: Introductionmentioning
confidence: 98%
“…However, a limited number of studies have quantified the impact of contextual improvement on food intake and/or on the nutritional status of institutionalized people (Abbott et al, 2013). Some of them focused on the effectiveness of a single change such as providing smaller portions (Cluskey & Dunton, 1999), switching from a prepared tray to a bulk service (Shatenstein & Ferland, 2000), having the staff share the meals with the residents (Charras & Frémontier, 2010), enhancing the colour contrast of the crockery that food was served on (Dunne, Neargarder, Cipolloni, & Cronin-Golomb, 2004), improving lighting (Brush, 2002) or diffusing music in the dining room (Ragneskog, Brane, Karlsson, & Kihlgren, 1996;Thomas & Smith, 2009). Six studies assessed large-scale changes which mainly aimed at shifting the dining room from an institutional appearance to more home-like setting ( Table 1).…”
Section: Introductionmentioning
confidence: 98%
“…In a controlled trial, implementation of a breakfast club resulted in increased communication and independence, interest and involvement [97]. Another controlled study in two special care units for persons with dementia in France reported positive effects on body weight and eating behavior as a consequence of shared mealtimes between residents and caregivers [98].…”
mentioning
confidence: 99%
“…Five of these intervention studies were quasi-experimental with a comparison group (45,56,57,61,83) while another five were a single group with a pretest-posttest design (40,53,(84)(85)(86). The final study had a posttest design and involved qualitative observations at seven sites that received the intervention (62).…”
Section: Staff Training and Support For Mealtime Activitiesmentioning
confidence: 98%
“…The comparison group quasi-experimental studies originated from France (56), United States (83), and Sweden (45,57,61). Charras investigated a training program implemented in one LTC facility (n ¼ 8) versus another facility with no training program put in place (n ¼ 10) (56). The 12 sessions focused on dementia training and shared mealtimes between staff and residents and emphasized the importance of resident-centered mealtimes (56).…”
Section: Staff Training and Support For Mealtime Activitiesmentioning
confidence: 99%
See 1 more Smart Citation